2021
DOI: 10.21037/tp-21-360
|View full text |Cite
|
Sign up to set email alerts
|

Early high-energy feeding in infants following cardiac surgery: a randomized controlled trial

Abstract: Background: Effective nutrition programs are beneficial for nutritional recovery in infants. Few studies have focused on the effect of early high-energy feeding after open heart surgery. This study sought to assess the effects of early high-energy feeding in infants after congenital heart surgery.Methods: Patients at a tertiary pediatric cardiology center who underwent open heart surgery between July 2016 and July 2018 were recruited and randomly allocated to 1 of the following 2 groups: (I) the intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Among two studies, reported median and interquartile range (IQR). 21 , 22 We manually calculated mean and standard deviation for these two studies using mean (SD) conversion formula. Dichotomous variables considered secondary outcomes and analyzed using RR formula.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among two studies, reported median and interquartile range (IQR). 21 , 22 We manually calculated mean and standard deviation for these two studies using mean (SD) conversion formula. Dichotomous variables considered secondary outcomes and analyzed using RR formula.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary outcomes reported six studies namely post-surgery infections (n=574) (RR=0.68, 95% CI: 0.43 to 1.08, P =0.40, I 2 =3%), 18 , 20 , 22 , 23 , 25 , 26 three studies reported vomiting (n=163) (RR=1.47, 95% CI: 0.80 to 2.69, P =0.90, I 2 =0%) 19 , 23 , 25 and three studies reported the mortality (n=218) [RR=0.42, 95% CI: 0.03 to 5.82, P <0.001, I 2 =80], 17 , 19 , 20 which was addressed by subgroup analysis of overall incidence of surgical complications [RR=0.88, 95% CI: 0.58 to 1.36, P 0.08, I 2 = 39], subgroup analysis stated [χ 2 =4.22, df=2, P =0.12] ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while conservative feeding practices are beneficial in reducing intolerance, they may, on the other hand, further reduce nutritional intake. Therefore, faced with the conflict between fluid restriction and insufficient intake, high energy formula can provide patients with more nutrition [ 24 , 25 ]. It is also possible to take a cue from another study and add pure whey protein isolate to formula [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional rehabilitation forms one of the cornerstones of critical care management of infants undergoing congenital heart surgery (CHS). [1][2][3] Malnutrition is common in infants with congenital heart disease (CHD) due to increased metabolic demands arising from the specific pathophysiology and decreased energy supply due to poor feeding abilities coupled with malabsorption. [4][5][6] In the perioperative period, this supply-demand mismatch is compounded by the effects of stress response to surgery, cardiopulmonary bypass (CPB), inotrope use, fluid restriction and delayed feeding.…”
Section: Introductionmentioning
confidence: 99%